A85 COLON CANCER SCREENING IN PATIENTS ASSESSED FOR LUNG TRANSPLANTATION. (26th February 2020) - Sanders, D; Telford, J J; Levy, R
Abstract: Background: Colorectal Cancer (CRC) mortality is significantly higher after a lung transplant (1). CRC screening for average risk patients in British Columbia is done with Fecal Immunochemical Testing (FIT) every two years (2), however colonoscopy is currently the standard modality in patients undergoing lung transplant assessments in British Columbia. The yield of using FITs or Fecal Occult Blood Testing (FOBT) and colonoscopy in screening for lung transplant assessments in Canada is unknown. Aims: To review the colon cancer screening results for all lung transplants done in British Columbia from 2013 to 2018. Methods: This is a retrospective chart review of the 222 lung transplants done from January 2013 to December 2019. Results: 220 patients were transplanted during this time period. 2 patients were re-transplanted. 136 of the 220 lung transplant patients were male (62%). The most common indication for transplantation was interstitial lung disease (44%), followed by chronic obstructive pulmonary disease (30%), cystic fibrosis (7%), and pulmonary hypertension (4%). Colonoscopies were performed in 127 of the 220 patients. Computed tomography (CT) colonography was performed in 15 of the 220 patients, and a FOBT or FIT was performed in 200 of the 220 patients. No colon cancers were found by colonoscopy or CT colonography (0/142). Of the colonoscopies performed, 38 % (49/127) had adenomatous or serrated polyps removed. Of these 36% (18/49) had high risk pathology. The positive predictive value of a FIT/FOBT positive for a polyp was 51.4 % (CI 37.6–65.1%). Conclusions: The value of non-invasive screening modalities in pre-lung transplant patients are modest. Program screening should be tailored to the lung transplant candidate's risk of CRC and the risk of an invasive procedure with a known complication rate. Funding Agencies: None